SISINGAAN SENI KEMASAN WISATA DI KABUPATEN SUBANG - Tubagus Mulyadi (Greget, 2009)
Artistry [of] Sisingaan represent Earing people resistance representasi symbol first to colonial practice a period of/to power [of] Dutch. Symbol Power grinding this implied in the form of appearance [of] lion idol which [is] stretcher. While resistance form depicted in moppet figure riding lion, please implies that grind will fail by the rising generation. Artistic [of] this tidiness [of] lebeih focussed [by] [at] show estetik facet, without eliminating meaning which consist in itKeyword : Sisingaan, artistic [of] tidiness